Post-migratory employment prospect: Evidence from Finland - Hannu Tervo (European Regional Science Association (ERSA), 1998)
This paper analyses the role which migration has in augmenting the likelihood of employment, by examining employment status of migrants and nonmigrants at the end of the migration interval on the basis of microdata. The paper continues the analysis of the paper by Tervo (1997) which examined the impact of unemployment on labour force mobility. Together these two papers address the role which interregional migration has as a labour market equilibrating mechanism. The empirical analysis is concerned with the situation of Finland. The data is taken from the Finnish longitudinal census data file from which a 1% sample has been taken. It contains data gathered at the censuses 1970, 1975, 1980, 1985, 1990 and 1995. The analysis is directed at those individuals belonging to the labour force, in which case the sample size is about 20 - 22 000, depending on the time period. The analysis deals with long-distance migration which is defined as occurring where an individual is resident in a different province from that five years earlier. The theoretical framework of the paper is in the job-search-model and human capital model of migration. For both the employed and unemployed, migration should augment the employability of migrants compared with nonmigrants if earnings potential is held constant. The direct impact of migration on re-employment is estimated with the help of logit regression, while holding constant the selectivity factors of migration and the marginal benefits and costs of search. In the estimations, a binary migration variable provides information on the comparative efficiency of job search between migrants and nonmigrants.
Keywords: 330